The Retention of DNA Data and the Private-life Interests of Suspects - Naudé, Bobby (Comparative and International Law Journal of Southern Africa, 2010)
The mere taking of DNA samples from someone has a direct impact on his/her private-life interests. This means that, any DNA collection and retention system that permits the indiscriminate collection of DNA samples from all suspects arrested upon any charge is constitutionally unsound. There is also no acceptable justification for the indefinite retention of such samples. DNA samples should be taken from suspects and arrested persons in terms of a warrant, and such samples, and the result of any forensic DNA analysis, should be destroyed once certain conditions have been met. It is further important that a court which finds a suspect guilty, should be the same body which orders the collection of DNA samples from that person. DNA data obtained from convicted offenders should be retained indefinitely, but provision should be made for an independent body that could consider requests to have information removed from any DNA databank.